Drivers of Banks’ Financial Performance - Te, Evans; Boadi, Lawrance Asari; Dadzie, Philomena (International Journal of Economics and Financial Issues, 2022)
A significant number of banks folded up during the Ghanaian banking financial crisis of 2017 to 2018 causing significant social costs as well as impeding economic growth. We take a step backward to present the significant drivers of the profitability of banks in Ghana. Obtaining panel data from the banks’ websites, the Ghana Statistical Service (GSS), and the Ghana Stock Exchange (GSE), the regression analysis was used to assess the drivers of profitability of banks in Ghana. The findings show that the bank-specific variables had no combined effect on profitability. Hence, the study concludes that the bank-specific variables do not have a significant influence on the performance of the Ghanaian listed banks. On the other hand, some of the external factors were observed to have a significant influence on profitability. The findings further showed that the drivers of profitability of the Ghanaian banks were, inflation, capital adequacy, and monetary policy. Since these are all external factors, the banks must learn how to predict and anticipate the external factors and make adjustments in their operations to enable them to improve profitability. While this study recommends to the managers of Ghanaian banks to be cautious in their operational decisions, the economy must also be managed soundly to ensure the growth of banks and hopefully avoid future crises.